Influence of Social Justice Advocacy on Multicultural Competence of University Undergraduates in Ondo State, Nigeria - Omiyefa, Muraina Olugbenga; Olorunjubee, Olatunji Israel (Advances in Social Sciences Research Journal, 2026)
The study identified social justice advocacy on multicultural competence of university undergraduates of university undergraduates in Ondo State, Nigeria. These was with a view to providing empirical information on social justice advocacy on multicultural competence of university undergraduates of university undergraduates in the study area. The study adopted the descriptive survey research design of Regression analysis. The target population of the study comprised 757 Social Studies university undergraduates in Ondo State. The sample for the study consisted of 500 undergraduates. Multistage sampling procedure was used to select sample for the study. Purposive sampling technique was used to select two out of the three Senatorial Districts (SDs) in Ondo State. The purpose was to choose SDs that have +universities offering Social Studies. One university was selected from each of the two SDs selected using simple random sampling technique while 250 undergraduates were selected from each of the universities using simple random sampling technique, making a total of 500 university undergraduates. Two research instruments were used to collect data for the study. These instruments Social Justice Advocacy Questionnaire (SJAQ) and Multicultural Competence Scale (MCS). Data collected were analysed using frequency, percentage, mean, and regression analysis. Results of the study showed that there was significant influence of social justice advocacy on multicultural competence of university undergraduates in Ondo State, Nigeria (F = 31.970; p < 0.05). This means that social justice advocacy influenced multicultural competence of university undergraduates in the study area. The study concluded that social justice advocacy influences multicultural competence of university undergraduates in the study area.